ANALISIS KOMPARASI BIAYA DAN JUAL EMISI KARBON, BIAYA PERAWATAN PEMBELIAN MOBIL LISTRIK, BIAYA OPERASIONAL MOBIL LISTRIK DAN TRANSISI DENGAN MOBIL KONVENSIONAL - Mantik, Ki Bagus; Sukadana, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 13 No 7 (2024): Vol.13.No.7. JULI 2024 [452-544], 2024)
Climate change is one of the impcts of increasing carbon emissions resulting from activities carried out by all living things. Tranpsortation, as a driver of community mobility, is one of the biggest contributors to invreasing carbon emissions. Electric cars as a means of transportation are considered to be a new breakthrough in reducing the level of carbon emissions in the Jakarta area. This research aims to determine the carbon emissions resulting from the use of electric cars and conventional cars, mainrenance costs, purchase prices and operational costs from the use of electric cars and conventional cars, and aims to determine the amount of carbon produced by electric cars compared to conventional cars. This research shows that electric cars have lower operational costs than conventional cars, however electric cars have quite expensive maintenance costs, so it is difficult to reach the general public because electric cars are quite new and ther are not yet enough types of electric cars. The Transition of all conventional cars in DKI Jakarta and Indonesia to electric cars shows that the use of electric caars can significantly reduce the level of carbon emission produced by conventional cars. keyword : Carbon Emission, Electric Car, Oil-Foeled Car, Analysist Data-t Statistic